A Survey-Based Analysis of Injuries to Horses Associated with Transport by Road in New Zealand - Riley CB; Rogers CW; Thompson KR; Guiver D; Padalino B (MDPI (Basel Switzerland), 2022)
Negative outcomes associated with the road transport of horses are a significant welfare issue. This study aimed to describe the injuries sustained by horses during road transport in New Zealand and factors associated with trauma while in transit. New Zealand horse industry participants were surveyed on their horse transport experiences and equine industry involvement. Participants were solicited through horse organisations. The data were tabulated, and a logistic regression was performed to identify significant (p < 0.05) factors associated with transport-related injury. In total, 201/1133 (17.7%/2 years) eligible surveys reported at least one horse injured during road transport. Most incidents occurred in transit (137/169; 81%), or when transported with one (76/193; 39.4%) or more (41/193; 21.2%) other horses. Most commonly, the hindlimbs, the head, or the forelimbs were injured (59.1%; 110/186 horses), ranging in severity from bruises to catastrophic orthopaedic trauma necessitating euthanasia. Eventing, not always checking horses' fitness for transport, using a tail guard or bandage, a stallion guard in the vehicle, bedding type on the floor, and behavioural problems were associated with injuries. This survey identified a significant incidence of injury and related death when horses are transported by road in New Zealand, and the key risk factors associated with the odds of injury.
Keywords: animal welfare; equine; horse; injury; road; survey; transport; transportation